The multiple roles of phosphate in muscle fatigue - Allen, David G.; Trajanovska, Sofie (Frontiers in Physiology, 2012)
Muscle fatigue is the decline in performance of muscles observed during periods of intense activity. ATP consumption exceeds production during intense activity and there are multiple changes in intracellular metabolites which may contribute to the changes in crossbridge activity. It is also well-established that a reduction in activation, either through action potential changes or reduction in Ca2+ release from the sarcoplasmic reticulum (SR), makes an additional contribution to fatigue. In this review we focus on the role of intracellular inorganic phosphate (Pi) whose concentration can increase rapidly from around 5 mM to 30 mM during intense fatigue. Studies from skinned muscle fibres show that these changes substantially impair myofibrillar performance although the effects are strongly temperature dependent. Increased Pi can also cause reduced Ca2+ release from the SR and may therefore contribute to the reduced activation. In a recent study, we have measured both Pi and Ca2+ release in a blood-perfused mammalian preparation and the results from this preparation allows us to test the extent to which the combined effects of Pi and Ca2+ changes may contribute to fatigue.